Giant permittivity in Nb-doped SrTiO3 single crystal: Compositional gradient and local structure. Issue 20 (15th October 2022) - He, Zichen; Cao, Minghe; Tao, Yong; Meng, Xiangyu; Wu, Jinsong; Hao, Hua; Yao, Zhonghua; Yu, Zhiyong; Liu, Hanxing; Furman, Eugene; Lanagan, Michael T.
Abstract: Nb-doped SrTiO3 single crystal exhibited a giant permittivity (>6.5 × 10 5 ) with an acceptably low dielectric loss (<10 −1 ) in a wide temperature range from −120 to 200 °C, making this material a good candidate for energy storage devices and modern microelectronics components. The mechanisms responsible for the giant permittivity of Nb-doped SrTiO3 single crystals were studied by means of microstructure characterizations, dielectric measurements, and density-functional theory calculations. A chemical compositional gradient extending from the surfaces was found, forming the internal barrier layer capacitance (IBLC) effect. Polar nanoregions (PNRs) were observed because of local fluctuations in distributions of Nb and oxygen vacancies. While both compositional gradients and local chemistry fluctuations increased polarization of the Nb-doped SrTiO3 single crystals, the local fluctuations dominated enhanced polarizability. This work suggests that optimizing local structures and chemistries in dielectrics is an effective way to tailor the desired dielectric performance.